Numerical simulation of airflow around vehicle models - Thang, Nguyen Van; Vinh, Ha Tien; Tri, Bui Dinh; Trong, Nguyen Duy (Vietnam Journal of Science and Technology, 2018)
This article carries out the numerical simulation of airflow over three dimensional car models using ANSYS Fluent software. The calculations have been performed by using realizable k-e turbulence model. The external airflow field of the simplified BMV M6 model with or without a wing is simulated. Several aerodynamic characteristics such as pressure distribution, velocity contours, velocity vectors, streamlines, turbulence kinetic energy and turbulence dissipation energy are analyzed in this study. The aerodynamic forces acting on the car model is calculated and compared with other authors.